The managerial conversion of senior civil servants: a convenient myth for the French local welfare state?. (March 2016) - Alcaras, Jean-Robert; Marrel, Guillaume; Marchand, Christèle; Nonjon, Magali
Has New Public Management really been rolled out homogenously across the board? Drawing on research into the viewpoints and practices of a particular category of senior civil servants in France (those in charge of local welfare policy), this article takes a critical look at this assumption of convergence towards NPM. Behind a discursive convergence that remains superficial and partial, the reality tends more towards heterogeneous and contextualized appropriations of New Public Management benchmarks often leading to new forms of bureaucracy. In a context where the position of public officials has been weakened, 'management' seems to have been adopted as a source of professional legitimization. By adopting this very useful managerial posture, these civil servants find comfort in perpetuating the myth of convergence. Points for practitioners: This article presents the results of a comprehensive study into the viewpoints and management practices of the roughly 500 senior civil servants in charge of local welfare policies in the French departments. How do they relate to the managerial vocabulary and management tools, given that their sector is characterized by contradictory reactions to economic and managerial rationales? The renewal of public management to which they contribute cannot be equated to an importation of methods that have shown their worth in the private sector: it seems above all to meet the new requirements on which their professional legitimacy must be built today.